الذكاء الاصطناعي وتقنياته: قضايا وتحديات في ضوء الفقه الإسلامي - ببوش محمد العربي; زعيم محمود (University of Eloued جامعة الوادي, 2024)
ملخص يهدف هذا البحث إلى إظهار أبرز وأهم التحديات من المنظور الفقهي الناتجة عن الذكاء الاصطناعي واستعمال تقنياته في مختلف نواحي الحياة الإنسانية، وقد تم ذلك من خلال التعريف بالذكاء الاصطناعي وبيان أهم مزاياه، ثم التركيز على أهم تحديين ناتجين عن استخدام تقنياته يستوجبان إعادة تجديد الاجتهاد الفقهي أولهما: الموثوقية في مجالي البحث العلمي والفتاوى الشرعية، وثانيهما: المسؤولية من خلال مجالات الأحوال الشخصية والمعاملات المالية والعقوبات الشرعية؛ وذلك باستخدام المنهج الوصفي التحليلي بشكل أساس، مع استعمال متفاوت للمنهج الاستقرائي. Abstract: This research aims to highlight the most significant challenges from a jurisprudential perspective arising from artificial intelligence and its use in various aspects of human life. This was achieved by defining artificial intelligence and stating its main advantages, then focusing on two major challenges resulting from its use that require renewing jurisprudential diligence: reliability in scientific research and religious edicts, and responsibility in personal status, financial transactions, and legal penalties. This is done using a descriptive-analytical approach primarily, with varying use of the inductive method. key words: challenges; artificial intelligence; issues; jurisprudential diligence
Keywords: تحديات، الذكاء الاصطناعي، قضايا، اجتهاد فقهي; challenges; artificial intelligence; issues; jurisprudential diligence